Pembentukan Komite dalam Penanggulangan Terorisme di Laut Lepas - Tomy Michael; Adetya Firnanda; Beni Winarta; Clarisa Turnip (LITERATUS, 2020)
This study aims to examine whether each country already has adequate laws to act against terrorism crimes, especially terrorism crimes that occur in the high seas. This research will use a statute approach and a conceptual approach. Problem formulation How do you deal with terrorism crimes that occur in the high seas? Since the establishment of the United Nations Convention on the Law of the Sea (UNCLOS) on December 10, 1982, world developments that have taken place for at least 37 years have been very rapid, including the dynamics that have taken place in regulating the high seas. Judging from its history, UNCLOS or the Law of the Sea Convention is an international treaty formed from the third United Nations Conference on the Law of the Sea which took place from 1973 to 1982. The emphasis of the Sea Law Convention is on rights and responsibilities countries in the management of the world's oceans as well as guidelines for the business, environment, and management of existing natural resources of the sea. Of all the crimes that occur in the high seas, which really should be a concern among countries that ratify the Law of the Sea Convention is about crimes of terrorism in the high seas. With the formation of this committee will help countries that do not yet have laws governing terrorism crimes. in the high seas in order to get justice and legal certainty due to the occurrence of terrorism that occurred. Each country must take part in overcoming and eradicating terrorism crimes in the high seas because of course without the same view on how terrorism in the high seas must be dealt with then no satisfactory solutions will be found that will further increase the risk of terrorism crimes on the high seas.